Experienced teammates increase productivity in remote work: Evidence from a full remote work company in Japan - Hideaki Ishikura (PLoS ONE, 2026)
This study examines peer effects among employees working fully remotely. We use panel data from a company that has operated with an entirely remote workforce since its inception and leverage as-if random assignment of new hires to teams as a quasi-natural experiment. We find no evidence that the average productivity of a worker’s teammates affects that worker’s own productivity. However, when team members are highly experienced, the productivity of employees on those teams increases by about 12.2%. In particular, employees with the shortest tenure see an increase in productivity of approximately 26.2%. Furthermore, this effect appears unrelated to the volume of communication within the team, suggesting that experienced teammates can have a positive influence even with minimal interaction, possibly through more efficient, targeted communication.